2016
DOI: 10.1136/bmjquality.u209049.w6736
|View full text |Cite
|
Sign up to set email alerts
|

Improving door-to-needle times for patients presenting with ST-elevation myocardial infarction at a rural district general hospital

Abstract: Acute coronary syndrome is a common condition with a major global impact on healthcare resources and expenditure. International guidelines are clear in specifying that patients with acute ST-elevation myocardial infarction (STEMI) should receive urgent coronary reperfusion with either primary percutaneous coronary intervention (PCI) or thrombolysis. Although PCI is the gold standard in the treatment of STEMI, this is not always achievable in a rural hospital with no cardiac catheterization service. Consequentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 24 publications
0
4
0
2
Order By: Relevance
“…In-service training with medical and nursing teams focused on recognition, investigation and management of STEMI and off-site ECG interpretation in a setting of clinical uncertainty. 25 Door-to-needle times improved from 43% baseline to 74% within 6 months post intervention. 25 Streptokinase causes significant delays and is used for patients at WWH.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…In-service training with medical and nursing teams focused on recognition, investigation and management of STEMI and off-site ECG interpretation in a setting of clinical uncertainty. 25 Door-to-needle times improved from 43% baseline to 74% within 6 months post intervention. 25 Streptokinase causes significant delays and is used for patients at WWH.…”
Section: Discussionmentioning
confidence: 89%
“… 25 Door-to-needle times improved from 43% baseline to 74% within 6 months post intervention. 25 Streptokinase causes significant delays and is used for patients at WWH. 26 Another study concluded that Tenecteplase (TNK) takes 10.5 min less time to prepare than standard treatment ( p < 0.001) with 18% more patients ( p < 0.01) meeting target times.…”
Section: Discussionmentioning
confidence: 89%
“…3 Na prática clínica, uma proporção significativa de pacientes não recebe atendimento que cumpra essas metas de tempo e a situação é ainda pior em comunidades rurais e áreas com poucos recursos. [3][4][5][6][7] Ainda faltam dados contemporâneos sobre o impacto do uso do atendimento pré-hospitalar no cenário do IAM, especialmente em países de baixa e média renda, principalmente na perspectiva mais generalizável de uma investigação de base comunitária, bem como informações sobre os resultados hospitalares de pacientes transportados por ambulância. No entanto, sabe-se que os primeiros minutos após o início do IAM são cruciais para o prognóstico e sobrevida do paciente e, considerando isso, é importante avaliar objetivamente os possíveis impactos do atendimento pré-hospitalar de emergência no manejo e nos desfechos do IAM.…”
Section: Introductionunclassified
“…Meta-analysis of randomized controlled trials maden by Vincent Roule et others [3] showed that compared with PPCI, prehospital fibrinolysis in the early period associated with better prognosis, included similar mortality rates, lower rates of cardiogenic shock, and higher rates of stroke in patients with ST-segment elevation myocardial infarction (STEMI). Despite the fact that the number of studies compared were relatively low, results supported an hypotise that prehospital FL with transfer to percutaneous coronary intervention (PCI) centers is a valid alternative to PPCI, which allows potential limitation of resources allocated to developing proximity 24/7 PCI facilities [4]. The benefit of PPCI over prehospital FL is not clear among patients managed early in the prehospital setting, but both of them are time-dependent with similar rates of mortality [3].…”
Section: Introductionmentioning
confidence: 99%